BLACK SEA-MARMARA SEA QUATERNARY CONNECTIONS: NEW DATA FROM THE BOSPHORUS, İSTANBUL, TURKEY - Kerey I.E.; Meriç E.; Tunoǧlu C.; Kelling G.; Brenner R.L.; Doǧan A.U. (My University, 2004)
Previous studies concluded that the Bosphorus Strait was formed during the Quaternary by fluvial incision of a valley between the Black Sea, to the north, and the Marmara Sea in the south. Hitherto, however, few details of the evolution of this connection have been elucidated from the sediments deposited within the Bosphorus itself. We report here details of sedimentological and palaeontological evidence relating to this history, obtained from five boreholes drilled into the unconsolidated sediment fill in the north-central sector of the Bosphorus, together with nearby geophysical profiles. The Quaternary fill of this part of the Bosphorus comprises two major facies associations. Yellow arkosic sands dominate the lower Facies Association A: these are assigned a Middle to Late Pleistocene age and the contained faunas have a lagoonal to lacustrine character and a Black Sea provenance (Paratethyan affinities). The abruptly succeeding units of Facies Association B comprise fining and coarsening upwards units of coarse to fine shelly and clayey sands that alternate with shell-bearing green clays. These sediments were formed in a range of marine and coastal settings and biostratigraphic evidence and absolute dating demonstrate the Mid–Late Holocene age of this upper unit. Initially brackish faunal assemblages in this upper unit show an upward increase in marine and Mediterranean affinities. Integrating these new data with previously published observations from coeval deposits in the southern Bosphorus and İzmıt Bay (NE Marmara Sea) we conclude that during the Late Pleistocene and Early Holocene a topographic barrier existed in the south-central sector of the Bosphorus, on both sides of which estuarine and lagoonal sediments accumulated, with distinctive Black Sea and Mediterranean faunas. During a significant rise in sea level, between 7000 and 5300 years ago, this barrier was finally submerged, permitting interchange of marine waters between the Mediterranean and the Black Sea and creating the present oceanographic situation. This evolution conflicts with the cataclysmic role of the Bosphorus in the early Holocene as postulated in the ‘Catastrophic Flood’ hypothesis of Ryan et al. [Mar. Geol. 138 (1997) 119–126; Annu. Rev. Earth Planet. Sci. 31 (2003) 525–554]. It also contrasts with the history recorded from the Gulf of İzmıt, where intermittent connection between these two bodies of water throughout much of the Quaternary is evident.
Keywords: Black Sea; Mediterranean; Quaternary; faunal affnities; facies associations; flood events; Cenozoic::Quaternary; Кайнозой::Четвертичная